Strategi Mengembangkan Manajemen Skill Agar Lebih Produktif Dan Efisien - Ira Setyawati; Shafira widya ramadhanti; Agung Winarno (PT. Hasba Edukasi Mandiri, 2025)
This article discusses strategies for developing managerial skills that can enhance productivity and efficiency within organizations. Effective managerial skill development is crucial in addressing the increasingly complex challenges faced by modern organizations. Several strategies discussed include training, mentoring, continuous learning, and the use of technology. By implementing these strategies, individuals and organizations can achieve significant benefits, such as improved decision-making, higher employee satisfaction, and better operational efficiency. However, there are various challenges to be faced, including resource limitations, organizational culture that does not support, and resistance to change. This article also suggests that organizations invest in managerial skill development and create a supportive learning culture to improve performance and organizational competitiveness.